Effectiveness of Prolonged Air-Recuring on Strength of Fire Damaged RC Columns - Muhammad Adeel Ehsan; Muhammad Yaqub; M. Uzair Khan; M. Umar Abdur rehman Amir; Iqrar Hussain (Civil Engineering Journal, 2019)
In this study, the effect of post-fire prolonged air-recuring on the recovery of strength of reinforced concrete was investigated after exposing to elevated temperature levels varying from 300 ºC to 900 ºC. The main objective of the paper is to find the effectiveness of prolonged air-recuring on strength of fire damaged RC columns. In order to achieve this, a total of 24 reinforced concrete circular columns having size  200 1200 mm were casted and tested under compressive loading. Eighteen specimens were heated in an electric furnace such that six specimens at each temperature level i.e. 300ºC, 500 ºC and 900 ºC. After heating, specimens were allowed to cool down naturally at ambient temperature and then specimens were air-recured in open environment (high humidity) following by repairing of respective specimens with various confinement techniques. After post fire prolonged air-recuring, test results showed that decrease in axial compressive at all temperature levels was less compared to values reported in literature for corresponding temperatures. This confirms the recovery of microstructure and thus increase in strength of post heated reinforced concrete circular columns due to prolonged air-recuring. It has been observed that both the confinement techniques i.e.  single layer of CFRP only and epoxy injection, steel wire mesh filled with epoxy resin mortar along with CFRP wrapping restored the original strength or even more of air-recured post heated reinforced concrete circular columns compared to that of un-heated control specimens or even more.